HUBUNGAN ANTARA FORGIVENESS DAN GRATITUDE DENGAN PSYCHOLOGICAL WELL-BEING PADA REMAJA DI PANTI ASUHAN X BEKASI - Pridayati, Tiaradika; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2019)
The research used is quantitative. This study aims to examine the relationship betweenforgiveness and gratitude with psychological well-being of adolescents living inorphanage ?X? Bekasi. Subjects totaled 103 adolescents. Techniques for retrieving datausing simple random sampling. Data analysis using bivariate correlation showed thatthere was a positive relationship between forgiveness and psychological well-being with r= 0.338 and p = 0,000 < p = 0.05. There is a positive relationship between gratitude andpsychological well-being with r = 0.505 and p = 0,000 <p = 0.05. Data analysis usingmultivariate correlation regression showed that there is a significant positive relationshipbetween forgiveness and gratitude with psychological well-being with R = 0.521 with p =0,000 < p = 0.05 and known coefficient of determination R Square of 0.272. Effectivedonations given forgiveness and gratitude to psychological well-being amounted to27.2%, while 72.8% were influenced by other factors not included in this study, includingotonomy, environmental mastery, purpose in life, and personal growth